Principal competency, teacher readiness, and teacher commitment in STEM education implementation: a qualitative study - Sariati Talib; Bity Salwana Alias; Mohd Effendi @ Ewan Mohd Matore (Penerbit Universiti Kebangsaan Malaysia, 2024)
The growing emphasis on Science, Technology, Engineering, and Mathematics (STEM) education in schools demands strong leadership and teacher commitment for effective implementation. However, challenges related to principal competency, teacher readiness, and their commitment have been identified as major obstacles to achieving desired outcomes through STEM initiatives. This qualitative study explores the competencies of school principals, teacher readiness, and the commitment required for successful STEM education. It aims to identify the principal competencies that influence teacher readiness and commitment, as well as the elements of teacher readiness that affect their commitment, and the specific aspects of teacher commitment crucial for STEM implementation. The study employs semi-structured interviews with teachers from selected schools, analyzed using thematic analysis to identify themes related to leadership competency, teacher preparedness, and commitment. Findings reveal that principals with competencies in STEM knowledge, management skills, and professional attributes are more likely to boost teacher readiness and commitment. Teacher readiness, particularly in terms of knowledge, skills, and attitude, plays a vital role in strengthening their commitment. Teacher commitment is driven by affective, continuance, and normative commitment, which are critical for STEM success. In conclusion, the study highlights the need to develop leadership competencies and teacher readiness as key strategies to enhance teacher commitment in STEM education. These findings have significant implications for education policy and professional development, calling for targeted interventions to support school leaders and teachers in effectively implementing STEM education.